The development of evidence-based classification of vision impairment in judo: A delphi study - Krabben, K. J.; Ravensbergen, R. H. J. C.; Nakamoto, H.; Mann, D. L. (Frontiers in Physiology, 2019)
Objective: Most para-sports group athletes into "classes" to compete against others with similar activity limitations. Judokas with vision impairment (VI) instead all compete in the same class irrespective of their level of impairment. There is considerable controversy whether this approach represents a legitimate way to structure judo competition. The aim of this study was to establish expert opinion on the requirements for an evidence-based classification system for VI judo.